Financial advisory and management system - Low, Xin Yin (2025)
The Financial Advisory and Management System project addresses the growing need for accessible, user-centric financial tools tailored for Malaysian users, focusing on empowering individuals to manage their finances effectively through advanced technology. This study develops an Android application using Kotlin and Firebase (Firestore) to enhance expense categorization, financial literacy, and goal tracking. The system enables users to create customizable expense categories, track spending with real-time data synchronization, and visualize financial trends through line and pie charts on the Transaction and Expenses Details Pages, ensuring accurate and flexible expense management. This financial education hub empowers users with personalized insights derived from their unique spending patterns and a community comparison feature that leverages real, anonymized data from other users. With the support of an AI assistant built on the Google Gemini API, the platform provides tailored, contextual advice to help users better manage their finances. Basic goal tracking functionality is implemented on the Goal Page, with plans to integrate the Days Needed Calculation Algorithm for real-time progress tracking in future iterations. The project employs a secure framework with Firebase Authentication, ensuring general data protection regulation (GDPR) compliance, and lays the foundation for future enhancements, including Google's ML Kit Text Recognition API integration for automated receipt scanning and Google's Speech Recognition API for using voice command to input the transaction. This research contributes to the field of personal finance technology by addressing limitations in existing systems, such as manual data entry and lack of financial education, through a free, culturally relevant solution designed for long-term financial stability.